Effects Of Financial Ratios On Financial Distress In Property And Real Estate Companies - Amelia Setyawati; Fanny Setyo Fidhyanti; Amelia Sugangga; Iradah Rahman (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The phenomenon of the Covid-19 pandemic has caused several property and real estate companies to experience financial difficulties. The domino effect of the Covid-19 pandemic has had a major impact on the economy, especially property and real estate companies. Many companies experience a decline in financial conditions that occurred before bankruptcy or can be called financial distress. This study aims to provide empirical evidence regarding the effect of profitability, liquidity, and leverage on financial distress. The number of companies that were sampled in this study were 23 companies listed on the Indonesia Stock Exchange (IDX) during the 2019 - 2020 period. The urgency of this research was carried out because in the current state of the economic crisis, it is necessary to organize a financial strategy through maximum profitability, liquidity, leverage will avoid Financial Distress on the company. The results of this study indicate that partially profitability (X1), liquidity (X2), leverage (X3) have a significant effect on financial distress in property and real estate companies. The results of the study also show that simultaneously profitability (X1), liquidity (X2), leverage (X3) have a significant effect on financial distress in property and real estate companies. Based on the results of these studies, this research has implications for investors and potential investors to be wiser in making investment decisions in a company, taking into account the condition and financial performance of the company and other factors so that the investment becomes more precise and generates the desired profit.